12.4k views
1 vote
What is the solution to the equation

What is the solution to the equation-example-1

1 Answer

3 votes

Answer:

The solution is:


x=-8

Explanation:

We have the following equation


-4(2x+3)=2x+6-(8x+2)

To solve the equation apply the distributive property


-4(2x+3)=2x+6-(8x+2)


-4*2x+3(-4)=2x+6-(1)*8x+2*(-1)

Now simplify the expression


-8x-12=2x+6-8x-2


-8x-12=-6x+4

Add 6x +12 on both sides of the equation


-8x-12+6x+12=-6x+4+6x+12


-2x=4+12


-2x=16

Divide both sides of the equality between -2


(-2)/(2)x=(16)/(-2)


x=-8

User Doobean
by
5.3k points